If it's not what You are looking for type in the equation solver your own equation and let us solve it.
180=(x+33)+(2x)
We move all terms to the left:
180-((x+33)+(2x))=0
We calculate terms in parentheses: -((x+33)+2x), so:We get rid of parentheses
(x+33)+2x
We add all the numbers together, and all the variables
2x+(x+33)
We get rid of parentheses
2x+x+33
We add all the numbers together, and all the variables
3x+33
Back to the equation:
-(3x+33)
-3x-33+180=0
We add all the numbers together, and all the variables
-3x+147=0
We move all terms containing x to the left, all other terms to the right
-3x=-147
x=-147/-3
x=+49
| y=320 | | v-2.3=4.82 | | -95/8m=154 | | (u-8)=7 | | 10n=160 | | x3+10=17 | | –3t+–10=–49 | | 3a+5=263a= | | -38+2x^2=60 | | 91.722-87.6=g | | 13w=5w+64 | | 3-(x+7)+2=6x-15+(-2x) | | 9y-3=-30 | | –7k+4=–6k | | 10/3=-5/2x | | q–4+ 7=4 | | -0.5m+-0.75=2.15 | | q/–4+7=4 | | 6x+10=-5x-34 | | –6w=7−7w | | (2y-8)+(3y-2)=180 | | 2(4x+2)+5x-2=-19 | | 2.4y+13+(-6.5y)=0.24y-8.85+(-6y) | | (5x)x2=(2x)x14 | | 7−9j=–8j | | -10-5y=-7y+10 | | –7+–3t=–19 | | ×-3=2x-3-x | | 9=4a+4 | | –3=6v | | 33/4=r×1/8 | | 8d−8=–8+8d |